Different engagement of TLR2 and TLR4 in Porphyromonas gingivalis vs. ligature-induced periodontal bone loss - Mei LIN; Yang HU; Yuhua WANG; Toshihisa KAWAI; Zuomin WANG; Xiaozhe HAN (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This study was conducted to investigate the roles of different Toll-like receptor (TLR) signaling in Porphyromonas gingivalis (P. gingivalis)-induced and ligature-induced experimental periodontal bone resorption in mice. Wild-type (WT), TLR2 knockout (KO), TLR4KO, and TLR2&4 KO mice with C57/BL6 background were divided into three groups: control, P. gingivalis infection, and ligation. Live P. gingivalis or silk ligatures were placed in the sulcus around maxillary second molars over a 2-week period. Images were captured by digital stereomicroscopy, and the bone resorption area was measured with ImageJ software. The protein expression level of gingival RANKL was measured by ELISA. The gingival mRNA levels of RANKL, IL-1β, TNF-α, and IL-10 were detected by RT-qPCR. The results showed that P. gingivalis induced significant periodontal bone resorption in WT mice and TLR2 KO mice but not in TLR4 KO mice or TLR2&4 KO mice. For all four types of mice, ligation induced significant bone loss compared with that in control groups, and this bone loss was significantly higher than that in the P. gingivalis infection group. RANKL protein expression was significantly increased in the ligation group compared with that in the control group for all four types of mice, and in the P. gingivalis infection group of WT, TLR2 KO, and TLR4 KO mice. Expression patterns of RANKL, IL-1β, TNF-α, and IL-10 mRNA were different in the P. gingivalis infection group and the ligation group in different types of mice. In summary, P. gingivalis-induced periodontal bone resorption is TLR4-dependent, whereas ligation-induced periodontal bone resorption is neither TLR2- nor TLR4-dependent.